PYTHON-BASED FUZZY TYPE-2 FOR PREDICTION MODEL - ZAMBRI, INTAN NADHIRAH (IRC, 2019)
A prediction model involves a high-level of uncertainties. Hence, Fuzzy Type-2 (FT2) is the enhanced version of fuzzy logic which has better capability in dealing with uncertainty problem. FT2 method was selected because it has better ability than Fuzzy Type-1 (FT1) and crisp methods in handling uncertainties. Besides, FT2 also has a better performance than General Type-2 (GT2). However, the implementation of Fuzzy Type-2 (FT2) has been widely used in today’s technology by using a Matlab and R programming language and it is hardly been seen that this method is been implemented using a Python language. Therefore, in this paper, it is proposed that the FT2 using Python language is developed for prediction model. This paper reviews previous research that are related to the FT2 in prediction model as well as the a software tools that has been used for the FT2 method.